EFFECTIVENESS OF HEALTH PROMOTION MEDIA IN IMPROVING PULMONARY TUBERCULOSIS PATIENTS' KNOWLEDGE OF THE HOME ENVIRONMENT - Sadya Bustomi; Fauziah Novriyani (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
Pulmonary tuberculosis (TB) remains a major public health problem in Indonesia. Preventing household transmission requires not only treatment adherence but also patients' knowledge of physical home-environment conditions, including ventilation, natural lighting, and residential density. This study aimed to analyze changes in pulmonary TB patients' knowledge of the physical home environment following health education delivered through leaflets, flipcharts, and educational videos in the service area of UPTD Puskesmas Banjar Agung. A quantitative approach with a quasi-experimental pretest-posttest design was employed involving 54 pulmonary TB patients, with 18 participants assigned to each of the leaflet, flipchart, and educational video groups. The intervention was conducted from November 2025 to January 2026 using equivalent educational content across the three groups. Knowledge was measured using a questionnaire before and after the intervention and analyzed using paired-samples t-tests at α = 0.05. The results showed an increase in knowledge in all three groups. The increase in the educational video group was statistically significant (p < 0.001), whereas the leaflet group reached the significance threshold (p = 0.050), and the flipchart group did not show a statistically significant change (p = 0.160). Based on the within-group analyses, the educational video group showed the strongest statistical evidence of improvement. However, this finding does not establish that video was statistically more effective than leaflets or flipcharts because no direct between-group comparison of changes was performed. Educational videos may therefore be considered a health promotion medium to strengthen pulmonary TB patients' knowledge of the physical home environment. ABSTRAK Tuberkulosis (TB) paru masih menjadi masalah kesehatan masyarakat di Indonesia. Pencegahan penularan di lingkungan rumah tangga tidak hanya memerlukan kepatuhan pengobatan, tetapi juga pengetahuan pasien mengenai kondisi lingkungan fisik rumah, seperti ventilasi, pencahayaan alami, dan kepadatan hunian. Penelitian ini bertujuan menganalisis perubahan pengetahuan pasien TB paru mengenai lingkungan fisik rumah setelah diberikan edukasi menggunakan media leaflet, lembar balik, dan video edukasi di wilayah kerja UPTD Puskesmas Banjar Agung. Penelitian menggunakan pendekatan kuantitatif dengan desain kuasi-eksperimental pretest-posttest yang melibatkan 54 pasien TB paru, masing-masing 18 peserta pada kelompok leaflet, lembar balik, dan video edukasi. Intervensi dilaksanakan pada November 2025–Januari 2026 dengan materi edukasi yang setara pada ketiga kelompok. Pengetahuan diukur menggunakan kuesioner sebelum dan sesudah intervensi, kemudian dianalisis menggunakan paired-samples t-test pada α = 0,05. Hasil menunjukkan adanya peningkatan pengetahuan pada ketiga kelompok. Peningkatan pada kelompok video edukasi signifikan secara statistik (p < 0,001), sedangkan kelompok leaflet berada tepat pada batas signifikansi (p = 0,050) dan kelompok lembar balik tidak menunjukkan perubahan yang signifikan (p = 0,160). Berdasarkan analisis dalam masing-masing kelompok, video edukasi menunjukkan bukti statistik peningkatan pengetahuan yang paling kuat. Namun, hasil tersebut belum dapat diartikan sebagai bukti bahwa video secara statistik lebih efektif dibandingkan leaflet atau lembar balik karena tidak dilakukan analisis perbandingan perubahan antarkelompok. Edukasi berbasis video berpotensi digunakan sebagai media promosi kesehatan untuk memperkuat pengetahuan pasien TB paru mengenai lingkungan fisik rumah.